Respuesta :
y=-1x+11.
I used an online graph for this and it would be tricky on paper.
I used an online graph for this and it would be tricky on paper.
This has a few steps. First, solve for m by plugging in x = 8, y = 3.
3 = 8m + 11 => m = -1. This is the slope of the equation. Now just plug this into the original equation.
So the solution is y = (-1)x + 11.
y = -x + 11
3 = 8m + 11 => m = -1. This is the slope of the equation. Now just plug this into the original equation.
So the solution is y = (-1)x + 11.
y = -x + 11